Aplikasi Kombinasi Pupuk NPK dan Pupuk Mikoriza terhadap Pertumbuhan Tanaman Terung (Solanum melongena L.) pada Fase Generatif - Restiani, Selvi; Saputra, Regi; Asti D, Arda; Pitaloka K, Diah; A, Fitrah; Anggraini, Selviana; Ma’shum, Halim; Siaga, Erna (LPPM Universitas Bina Insan, 2024)
The eggplant is a popular fruit and vegetable plant known for its delicious taste. Eggplant farming is economically valuable due to high market demand. Proper fertilization during the generative phase is essential for increasing eggplant production. This study investigates the effects of Pearl NPK 16-16-16 fertilizer and Mycorrhiza Fertilizer on eggplant growth and production. Conducted at the Experimental Land of the Agrotechnology Study Program, Faculty of Plant and Animal Sciences, Universitas Bina Insan, the research employed a Completely Randomized Design (CRD) with treatments: P0 = 0 g NPK Fertilizer + 10 g Mycorrhiza Fertilizer, P1 = 5 g NPK Fertilizer + 10 g Mycorrhiza Fertilizer, P2 = 10 g NPK Fertilizer + 10 g Mycorrhiza Fertilizer, and P3 = 15 g NPK Fertilizer + 10 g Fertilizer. The study revealed that the treatments significantly impacted plant height, leaf count, root weight (wet and dry), total weight, and dry weight of roots, stems, leaves, and overall eggplant plants. Application of 10 g NPK Fertilizer + 10 g Mycorrhiza Fertilizer (P2) yielded the best results in plant height, leaf count, wet and dry weight of plants, differing significantly from P0, P1, and P3 treatments.